The Attitudes of Residents towards Agro-tourism Impacts and Its Effects on Participation in Agro-tourism Development: The Case Study of Vietnam - Nha Thi Huynh Nguyen; Suvit Suwanno; Weerapon Thongma; Parichart Visuthismajarn (My University, 2018)
The Attitudes of Residents towards Agro-tourism Impacts and Its Effects on Participation in Agro-tourism Development: The Case Study of Vietnam
Keywords: Resident attitudes; Agro-tourism; Tourism participation